Clinical outcomes of DSAEK with pre-cut grafts of thickness more than 150 microns - Aravind Roy; Tanvi Mudgil; Nikita Das; Megana Peddi; Sunita Chaurasia (Indian Journal of Ophthalmology)
Purpose: To study the clinical outcomes of descemet stripping automated endothelial keratoplasty (DSAEK) with pre-cut lenticules of thickness above 150 microns. Methods: During the study period Jan 2019 to Sept 2020, 1865 pre-cut DSAEK lenticules were prepared at the institute-affiliated eye bank by two trained technicians. Of these, 28 (1.5%) grafts had a thickness >150 microns and were utilized at the institute. Retrospective review of medical records was performed for these patients. Results: Median donor age was 39 (range, 20–62) years, death to preservation time was 6 (range, 0.28–8.4) hours, endothelial cell density (ECD) was 2738 (range, 2203–3788) cells/mm2, graft thickness was 186 (range, 170–250) microns. The mean recipient age was 58 (range, 36–76) years, and 17 were males. The most common indication for surgery was pseudophakic corneal edema (n = 14, 50%). The mean log MAR visual acuity at 1-month, 3-month, and 6-month post-operative visits improved to 0.8, 0.7, and 0.5, respectively. The mean lenticule thickness at 3- and 6-month post-operative period reduced to 161 and 151 microns, respectively. Graft detachment needing rebubbling in 5/28 (17.8%) eyes. Primary graft failure was noted in six (21.4%) eyes, which included one eye that underwent rebubbling. Secondary graft failure was noted in four eyes (14.2%). Eighteen (81.8%. 18/22) eyes were maintained graft clarity till the end of the study period, mean follow-up of 10.5 (range, 3–18) months. Conclusions: With the currently practiced nomograms in automated methods of DSAEK graft preparation, graft thickness over 150 microns can occur infrequently (<1.5%); however, DSAEK lenticules above150 microns can have a favorable outcome in large majority (81.8%). The study noted rebubbling and primary graft failure rate in a fifth of all eyes with lenticule thickness > 150 microns.